A network analysis of nutrition stakeholders in Odisha - Kohli, Neha; Pradhan, Mamata; Menon, Purnima (International Food Policy Research Institute, 2014)
This nutrition stakeholder analysis is based on data gathered through a participatory interview technique called Net-Map. Net-Map identifies key stakeholders who are relevant to an issue, maps the links among these stakeholders, and describes their power over the specific issue. It has been used widely in policy and stakeholder analyses. The Net-Map interview in Odisha was facilitated by the International Food Policy Research Institute (IFPRI), New Delhi, with support from the Department of Women and Child Development, Odisha.